Technological Adaptation Trends for Sociology Teachers in Online Learning during Covid-19 Pandemic - Ni Kadek Marhaeni Desyantari; I Wayan Putra Yasa; I Gusti Made Arya Suta Wirawan; Lola Utama Sitompul; Irwan Nur (Universitas Pendidikan Ganesha, 2023)
Online learning during the COVID-19 pandemic has forced sociology teachers to adapt to technology as a supporting medium, so that teaching and learning activities can be carried out correctly. The research method used in this research is the descriptive qualitative method. The research data are the results of interviews and observations. Sources of research data are sociology teachers in Singaraja City High School. Data collection techniques using observation and interviews. The data analysis technique is triangulation using (1) data reduction, (2) data presentation, and (3) concluding. This research indicates that sociology teachers use some aplications to support their online learning activities. However, some of these applications that are most often used include WhatsApp Group, Google Classroom, and Educandy as a game education. The main reasons why they use this application because it was faster, more effective and efficiently. The obstacles experienced by sociology teachers are the lack of ability to adapt to available technology so that sociology teachers only use three supporting application, and students who do not have signals, quotas, and cell phones become obstacles for sociology teachers in delivering material and assignments to the students concerned. And student delays in collecting assignments are obstacles for sociology teachers in providing assessments. The solutions taken are IT mastery training, the use of learning videos, educational games, and students who are constrained by signals and quotas can visit schools.